An adult choledochocele case presented with gastric outlet obstruction: A rare presentation - Mehmet Fatih CAN; Nihat KAYMAKÇIOĞLU; Gökhan YAĞCI; Semih GÖRGÜLÜ; Turgut TUFAN (Turkish Journal of Gastroenterology, 2019)
-